Pemanfaatan Lingkungan Sekolah dan Keluarga Sebagai Pendidikan Positif bagi Anak dalam Belajar di SD Negeri 135 Kota Jambi - Sari, Pratiwi Indah (Jurnal Ilmiah Dikdaya, 2022)
This study aims to determine the picture of the school and family environment on children's positive education in participating in the learning process, and to know the impact of the role of schools and families for children's success in learning at SD Negeri 135 Jambi City. This research design uses descriptive qualitative. Meanwhile, the technique in this study uses purposive technique, namely the determination of informants is not based on guidelines or based on population representatives, but is based on the depth of information needed related to the research problem. The results showed that: 1) Teachers tend to understand that positive education has the same meaning as psychology, thus leaving all problems that arise between students to the counseling teacher, 2) Parents only leave it to schools to be able to provide knowledge and educate their children without making further interactions while in home.